The community structure of mangroves in Barangay Cabanbanan, Oton, Iloilo. - Gomez, Dee Miro
Mangroves are tropical trees, shrubs, vines and palms that grow along coastal waters, tidal flats, extending along rivers, streams and its tributaries where the water is brackish . This study aims to assess the community structure of mangroves in Barangay Cabanbanan, Oton. Themangrove area was studied using the transect line plot method. Nine plots were established in the sampling site. A total of eleven mangrove species belonging to six families were present in the area. The seven families are Family Avicenniaceae represented by Avicennia alba, Avicennia marina, Avicennia officinalis, Aviecennia rumphiana; Family Euphorbiaceae represented by Exoecaria agallocha; Family Rhizophoraceae represented by Bruguiera cylindrica, Ceriops decandra, Rhizophora apiculata; Family Sonneratiaceae represented by Sonneratia alba; Family Combrataceae represented by Lumnitzera racemosa and Family Lythraceae represented by Pemphis acidula. community structure of mangroves in Barangay Cabanbanan, Oton ahowed the following results: Avicennia alba has the highest average stand basal area of 21.445 (m2/ha) while Sonneratia alba had the lowest stand basal area of 0.362(m2/ha)). Avicennia alba has the highest average density of 43 tree/ha while Thizophora apiculata has the lowest with 0. Avicennia alba and Avicennia marina had the highest relative frequency of 17.94 percent while Pemphis acidula had the lowest with 2.564 percent. Avicennia alba is the dominant species with a relative dominance value of 39.337 while Sonneratia alba had the lowest value of 0.717. Avicennia alba is the most important species in the area with an importance value of 84.683 and the least importance species is Sonneratia alba with a value of 1.507. The area is considered diverse with index of diversity of 0.821. The area is sheltered and less disturbed from human interventions and it offers a suitable environment for different species to thrive. The interplay of physico-chemical and biological factors further contributed to the observed diversity of mangroves in the area.